Finger Painting Activities to Develop Fine Motor Skills in Children Aged 4-5 Years - Ulfi Nur Hidayah; Leli Fertilianan Dea; Yuning Eka Rahma Wati (CV. Creative Tugu Pena, 2024)
This study aims to determine the implementation of finger painting activities in developing fine motor skills of children aged 4-5 years at PAUD Istiqomah, Sri Basuki Village, Batanghari District. Using a qualitative approach, this study emphasizes the process through direct observation, in-depth interviews, and documentation of nine children selected purposively. The results of the study indicate that finger painting activities are able to effectively improve children's fine motor skills, such as eye and hand coordination, the ability to use writing tools, as well as creativity and self-confidence. In addition to the physical aspect, this activity also supports children's emotional and social development through a fun, creative expression space. Thus, finger painting is proven to be an art-based learning method that has high educational value and is worthy of being included in the early childhood education curriculum.